Mapping the walls: High-resolution cartography applied to the analysis of prehistoric cave art in the Grotte du Mammouth (Domme, Dordogne, France). (March 2021) - Le Fillâtre, Virginie; Robert, Eric; Petrognani, Stephane; Lesvignes, Emilie; Cretin, Catherine; Muth, Xavier
Abstract : The analysis of paintings and engravings on the walls of Upper Palaeolithic caves generally focuses on the images themselves, their technical or stylistic characteristics, graphical and spatial composition, and, to a lesser extent, radiometric dating. More recent studies of cave art have reinforced new interdisciplinary perspectives that address the archaeology, karstology and geomorphology of the site. This latter aspect helps place the representations in the long-term geo-morphological history of the cave itself, and thus sheds new light on its human occupation. At the Grotte du Mammouth (Domme, Dordogne, France), we developed an innovative approach to cave art that incorporates a geological and geomorphological analysis of the decorated walls combined with new mapping and digital recording techniques to produce a detailed "identity card" of the site's features. Highlights: An innovative and integrated archaeological and geomorphological method to map the parietal art. Detailed catalogue of karstic features available in the Grotte du Mammouth to compare archaeological and geological markers. Identification of karstic features associated with each panel to interpret certain graphic entities or to clarify others. Combining geological and archaeological data to distinguish natural processes from cave art on the walls. A relative chronology of most natural phenomena regarding the anthropogenic representations. The cave walls shapes, sediments and chemical deposits used in order to retrace the cave wall history over the long term.